1984
DOI: 10.1016/0008-8749(84)90394-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating properties of two synthetic adjuvants: Dependence upon type of antigen, dose, and time of administration

Abstract: The effects of two synthetic adjuvants on the antibody response to sheep red blood cells (SRBC) as a thymus dependent (TD) antigen and to dinitropheny&s-Ficoll as a thymus-independent (TI-1) antigen were investigated in mice. Both dimethyldioctadecylammonium bromide (DDA) and dextran sulfate (DXS) augmented the humoral response to SRBC but not to dinitrophenylJgFicoll if injected simultaneously with antigen. Dose-response curves of both antigen and adjuvant revealed that DXS compared to DDA is a more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…injection of cationic lipids showed defective secretion of NO and TNF‐α when activated by LPS. Hilgers et al (1984) have also shown that the i.p. injection of positively charged liposomes can modulate the immune system.…”
Section: Discussionmentioning
confidence: 90%
“…injection of cationic lipids showed defective secretion of NO and TNF‐α when activated by LPS. Hilgers et al (1984) have also shown that the i.p. injection of positively charged liposomes can modulate the immune system.…”
Section: Discussionmentioning
confidence: 90%
“…However, binding of DDA to antigens is not always essential for its adjuvant activity. Interaction with macrophages brings about release of cytokines (including interferon), depresses antigen degradation and prolongs antigen persistence [20,21,25,34]. Moreover, since isotype switching and DTH, which are affected by DDA so efficiently, are both dependent on the TH1 subset of T helper cells through the production of IL-2 and interferon y [35] it can be assumed that DDA has a direct or an indirect influence on those lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation for the evaluation of adjuvant activities of aliphatic nitrogenous bases several substances possessed immunostimulating effects and amongst them was a quaternary ammonium lipoid compound, dimethyl dioctadecyl ammonium chloride (DDA) [16]. The adjuvanticity of the bromide derivative of this substance was extensively tested in a variety of laboratory animals in combination with proteins and haptens [16][17][18], red blood cells [19][20][21] tumour cells [22] and viruses [23][24][25][26][27]. DDA was also tried in humans in conjunction with tetanus toxoid vaccines [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…As already discussed in our previous paper [10] there is no agreement as to the exact mechanism of action of DDA. One group of authors mantains that the adjuvanticity of DDA is independent of the presence of antigen [20][21][22][23] while others have shown the importance of direct binding of the antigen to DDA or simultaneous addition of the DDA and antigen at the same inoculation site [24][25][26]. In the present study, DDA vaccines which contained NDV antigen preparations of different purities were compared ( Table 3).…”
Section: Discussionmentioning
confidence: 99%